FKR : an efficient authentication scheme for IEEE 802.11ah networks - Zhang, Lyuye (2022)
IEEE 802.11ah is a recently published standard for low-rate wireless communications over smart devices used for Internet of Things (IoT) systems. As a member of 802.11 Wireless Local Area Network (WLAN) protocol family, it presents a fine solution to extend the life of a network of resource-constrained devices and enhance the efficiency of low-rate communications. Although the performance of the Media Access Control (MAC) layer has been improved, the security functionality, especially for the authentication, is inherited from the legacy version. Lightweight authentication protocols to support the IoT devices with the requirements of low-power consumption and low-latency are much demanded. To meet the new demands, in this paper, an enhanced authentication scheme based on Fast Initial Link Setup (FILS) specified in IEEE 802.11ai standard is proposed, named as Fast Key Re-authentication, (FKR). It is designed for the authentication process in the link setup procedure to improve the overall performance of the 802.11ah networks.